Dual-recognition colorimetric sensing of thrombin based on surface-imprinted aptamer–Fe3O4. Issue 20 (19th May 2021) - Shen, Mingmei; Wang, Yuanyuan; Kan, Xianwen
Abstract : A convenient and effective colorimetric approach was developed for the sensitive and selective detection of thrombin based on blocking the peroxidase-like activity of inner Fe3 O4 nanoparticles by the adsorption of thrombin in imprinted cavities. Abstract : Thrombin plays an essential role in blood coagulation and some physiological and pathological processes. The convenient, rapid, sensitive, and specific detection of thrombin is of great significance in clinical research and diagnosis. Herein, surface molecularly imprinted polymer (MIP) was modified on aptamer-functionalized Fe3 O4 nanoparticles (MIP–aptamer–Fe3 O4 NP) for thrombin colorimetric assay by taking advantage of the peroxidase-like activity of Fe3 O4 NP. With the adsorption of thrombin into imprinted cavities, the exposed surface area of Fe3 O4 NP decreased, causing a decrease in its peroxidase-like activity toward 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2 O2 . On the other hand, the reductive amino acids on the thrombin surface also impeded the oxidation of TMB. Both phenomena caused the light blue color of the sensing solution. Thus, a specifically sensitive colorimetric approach for the visual detection of thrombin was proposed with a linear range and limit of detection of 108.1 pmol L −1 –2.7 × 10 −5 mol L −1 and 27.8 pmol L −1, respectively. Moreover, due to the double recognition elements of MIP and aptamer, the prepared MIP–aptamer–Fe3 O4 NP showed higher selectivity to thrombin than that based on only one recognition element. It is worth noting that no special property ( e.g. electrochemical or fluorescence activity) of the template was required in this work. Thus, more template molecules can be easily, selectively, and sensitively detected based on the proposed MIP–aptamer–mimic enzyme colorimetric sensing strategy.